Enzymatic Modifications of Chitin, Chitosan, and Chitooligosaccharides - Kaczmarek, Michal Benedykt; Struszczyk-Swita, Katarzyna; Li, Xingkang; Szczęsna-Antczak, Miroslawa; Daroch, Maurycy (Frontiers in Bioengineering and Biotechnology, 2019)
Chitin and its N-deacetylated derivative chitosan are two biological polymers that have found numerous applications in recent years, but their further deployment suffers from limitations in obtaining a defined structure of the polymers using traditional conversion methods. The disadvantages of the currently used industrial methods of chitosan manufacturing and the increasing demand for a broad range of novel chitosan oligosaccharides (COS) with a fully defined architecture increase interest in chitin and chitosan-modifying enzymes. Enzymes such as chitinases, chitosanases, chitin deacetylases, and recently discovered lytic polysaccharide monooxygenases had attracted considerable interest in recent years. These proteins are already useful tools toward the biotechnological transformation of chitin into chitosan and chitooligosaccharides, especially when a controlled non-degradative and well-defined process is required. This review describes traditional and novel enzymatic methods of modification of chitin and its derivatives. Recent advances in chitin processing, discovery of increasing number of new, well-characterized enzymes and development of genetic engineering methods result in rapid expansion of the field. Enzymatic modification of chitin and chitosan may soon become competitive to conventional conversion methods.